2019
DOI: 10.1016/j.atherosclerosis.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection selectively increases the risk for carotid atherosclerosis in young males

Abstract: Background and aims-Atherosclerosis is an important contributing factor to cardiovascular mortality. The role of Helicobacter pylori (H. pylori) infection in atherosclerosis is inconsistent and sometimes controversial. The present study aimed to determine if H. pylori infection is associated with carotid atherosclerosis. Methods-17,613 males and females with both carotid ultrasonic examination and 13 C-urea breath test for H. pylori infection were screened by a major Chinese university hospital from March 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 44 publications
7
39
0
2
Order By: Relevance
“…Several observational studies have linked chronic infection with H pylori to ischemic CVD, thrombotic cerebrovascular disease, and peripheral vascular disease 8‐10 . Some previous studies also showed that H pylori infection can increase the risk of CVDs, especially in the early life 11‐13 . However, other studies have suggested that chronic infection with H pylori was not strongly associated with adverse cardiovascular events such as coronary heart disease or stroke after adjusting for age, sex, and other risk factors, nor was CagA‐positive strain strongly associated with coronary heart disease compared to other strains 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies have linked chronic infection with H pylori to ischemic CVD, thrombotic cerebrovascular disease, and peripheral vascular disease 8‐10 . Some previous studies also showed that H pylori infection can increase the risk of CVDs, especially in the early life 11‐13 . However, other studies have suggested that chronic infection with H pylori was not strongly associated with adverse cardiovascular events such as coronary heart disease or stroke after adjusting for age, sex, and other risk factors, nor was CagA‐positive strain strongly associated with coronary heart disease compared to other strains 14‐16 .…”
Section: Introductionmentioning
confidence: 99%
“…The data showed that for males with age of <50 years, there was a 22.5% increase in the prevalence of carotid atherosclerosis in the subjects with H. pylori infection compared with the ones without H. pylori infection. These data demonstrated that H. pylori infection selectively increased the risk for carotid atherosclerosis in young males under 50 years old [47]. However, how H. pylori infection could lead to atherosclerosis, and why only in young males is unknown.…”
Section: Helicobacter Pylori Infection and Carotid Atherosclerosismentioning
confidence: 82%
“…Recently, a large patient database of 17,613 adult patients with carotid ultrasound examination and a 13 C-urea breath H. pylori test was analyzed [47]. Based on the study designs, the patients were divided into two groups: a cross-sectional study for single measurement group, and a retrospective cohort study for the patients with follow up measurements up to 5 years.…”
Section: Helicobacter Pylori Infection and Carotid Atherosclerosismentioning
confidence: 99%
“…21 In a prospective Chinese study, including 17 613 patients screened with both carotid ultrasound examination and 13 C-UBT, H pylori infection was an independent risk factor for prevalent and incident carotid atherosclerosis only in males under 50 years (P = .009 and P = .028, respectively). 22 To support the role of H pylori infection in the pathogenesis of CHD via endothelial damage, Li…”
Section: Ard I Ova Scul Ar and Cereb Rova Scul Ar D Is E A S E Smentioning
confidence: 99%